Service Quality and Customer Satisfaction In the Hotel Industry: Examining the Role of Service Excellence in Ensuring Guest Satisfaction (Journal of Advances and Scholarly Researches in Allied Education, 2014)
This paper attempts to illuminate the role of serviceexcellence in creation of satisfactory guest experience in the hotels in India.Most popular hotels of Oberai and Taj group and others were selected for thepresent research, and opinions of the hotel’s guests were sought for assessingthe perception of the guests in five primary dimensions of service excellence.